Streptococcus pneumoniae in urinary tracts of children with chronic kidney disease - Burckhardt, Irene; Zimmermann, Stefan (Emerging infectious diseases, 2011)
Streptococcus pneumoniae is not commonly considered an agent of urinary tract infections. We report 3 children with urinary tract abnormalities who had high numbers of S. pneumoniae in their urine (>104 CFU/mL) and varying clinical symptoms.
Gesehen am 24.06.2022